Displacements of reinforced slopes subjected to seismic loads - Michalowski, Radoslaw L.; You, Liangzhi (American Society of Civil Engineers, 2000)
Traditional analyses of stability of slopes subjected to seismic loads entail global equilibrium considerations with seismic influence included as a quasi-static force. Such an analysis does not reflect the earthquake shaking process, and it does not provide any information about permanent displacements that may have occurred as a result of that process. Earthquake events in recent years have brought about renewed interest in analyses of slopes subjected to seismic loads. This paper focuses on displacement calculations of reinforced slopes. Design of reinforced slopes using the quasi-static approach may lead to an unrealistically long reinforcement for large ground accelerations. If slopes are allowed to move by even a small displacement, then the reinforcement length can be reduced significantly. Two mechanisms of failure of reinforced slopes subjected to seismic conditions are considered: (1) rotational collapse; and (2) sliding directly over the bottom layer of reinforcement. Yield accelerations and integrals of seismic records are presented in charts for easy use in practical applications. An example is shown to illustrate the method." -- Authors' Abstract